THE THEORY AND METHODOLOGY OF GEOPHYSICS MONITORING OF DANGEROUS GEOLOGICAL PROCESS - VYZHVA, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The theory and methodology of geophysics monitoring of dangerous geological process on the basis of nonlinear multicomponent crack model of geological medium are proposed. Mathematical modeling of effective geophysical parameters with the help of the method of conditional moment functions taking into function of minerals and cracks, mode of deformation, pressure and temperature are described. Nonlinear parameters and acoustoelastic effects into medium with initial effort are considered. Statistical modeling of random processes and fields for increase number of realization are proposed.